Social Interactions Among Undergraduates at State Universities: An Analysis of Experiences Post-Easter Sunday Terrorist Attacks - Iqbal Saujan; MHA. Munas; Mohamed Mubarak Mohamed Rasmy; Mohamed Ashraff Fathima Anfaal (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
Sri Lanka is a country with diverse religions and ethnicities. Sri Lanka’s Muslim-Buddhist relationship dates back centuries. Its diverse background is due to its long history of religions, cultures, and ethnic groups. Because of tension and enmity between different ethnic groups, ethnic conflict is frequent. Exactly this happened with the Easter Sunday bombings on 21 April 2019. The main objective of this study is to examine whether the criticism and hate speech that occurred after the Eastern Sunday attack affected the social interaction of university students. The researchers used a mixed method of study through an empirical approach. The data for the study were collected by distribution of 268 questionnaires and 25 unstructured interviews. The questionnaire data were analysed with the help of SPSS software (version 26); interview transcriptions underwent a coding analysis method. According to the findings, There was a healthy social interaction between the undergraduates of the two religions. Nevertheless, factors that hinder mutual contact include frequent meetings with the same religious students and being threatened by one's religious friends when developing good relations with a person belonging to another religion. Several parameters need to be met for a healthy social co-existence to be built on mutual understanding, including a lack of understanding of other religious beliefs and a lack of interest in learning other recipes. It is likely that if this situation continues in the future, tensions will arise between Muslims and other students at the university.